Study of The Influence of Extract Cocoa Pods (Theobroma Cacao) as a Preservative Ingredient on Mahoni Woods (Swietenia Mahogany) Through Cold Soaking on Mechanical Properties - Anhar, Muh; Yusuf, Yusuf; Ruchiyat, Asep; Suhelmidati, Etri; Putra, Syarif Abdian; Danial, Danial; Yetri, Yuli (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2024)
An attempt has been made to extend the service life of mahogany wood (Swietenia mahogany) by preserving it. The purpose of this study was to determine the mechanical properties of mahogany wood after cold soaking with preservatives of cocoa pods extract (Theobroma cacao). This research uses an experimental method of cold soaking which is carried out in the Material Testing Laboratory of the Mechanical Engineering Department of Padang State Polytechnic. The preservation process used cacao pod extract preservative solution at concentrations of 0%, 3%, 6%, 9%, 12%, and 15%. The observed responses were the preservative retention values and mechanical properties (compressive strength parallel to the fiber direction, flexural strength, and surface hardness) of the wood. The preservation method applied was cold soaking for 120 hours. The increase in retention value was directly proportional to the increased concentration of extract added. The improved properties of wood (compressive strength in the grain direction and flexural strength) also increased with increasing extract concentration. The results obtained showed that the highest value was obtained at a 15% concentration of the added extract with a retention of 7.6078 kg/cm2, a compressive strength parallel to the fiber of 227.92 kg/m2, and a flexural strength of 387.82 kg/m2. This data shows that cocoa pods extract has the potential to be used as an environmentally friendly wood preservative.